Dynamics of Proteins by Thermal Decay of Free Radicals Induced by Ultraviolet Irradiation - Rasim B. Aslanov; Leman M. Dashdemirova; Oktay Z. Alekperov; Azad R. Abdurahimov; Oktay K. Gasymov (Journal of Spectroscopy)
The relationship between structure, dynamics, and function of biomolecules is a fundamental interest of biophysics. Protein dynamics drastically vary in temporal and spatial scales. The function of a particular protein determines the significance of a distinct type of dynamics. Here, we investigate the influence of hydration water on the dynamics of a protein called silk fibroin. Particular interest is to investigate the protein dynamics using thermal decay of the free radicals induced by ultraviolet irradiation. The full decay of the free radicals occurs at very wide temperature region (120 K–340 K). Three distinct regions with transition points of ∼135 K, 205 K, and 279 K are apparent in the thermal decay curves of hydrated fibroin samples. The first transition (∼135 K) that leads 2–6% increase of total spins was observed only in the decay curves of fibroin submerged in 40% and 50% glycerol. The second transition (∼205 K) was invariant for all samples, hydrated and dry fibroins. The third transition of 279 K common for all hydrated fibroin samples was shifted about 84 K to a higher temperature of 363 K in dry fibroin. The thermal transitions at 205 K and 279 K are weakly and strongly, respectively, coupled to water molecules. Nature of the free radicals participated in these transitions was identified. The significance of the findings for protein dynamics is discussed.